Social Interaction Between Mountaineers And Climbing Guides In Enhancing Mountain Safety Awareness - Ale Zidane Saputra; Khaerudin Imawan; Rahmayanti (Journal of Science and Education (JSE), 2025)
Mountain climbing is becoming increasingly popular as a recreational and adventure activity, but this trend is accompanied by an increased risk of accidents due to a lack of safety awareness. This study aims to examine the communication patterns used by the climbing community and trail managers in an effort to raise awareness of the importance of safety in climbing areas. The approach used is descriptive qualitative, with data collection techniques including interviews, observations, and document analysis. The Activity, Interaction, Sentiment (AIS) theory is used as the analytical framework, focusing on three aspects: activity, interaction, and sentiment. The research findings indicate that group communication strategies are carried out in three main stages. First, activity, which includes hiking briefings, education about risks, and checks on equipment and logistics. Second, interaction, which involves the exchange of information among members regarding hiking trails, weather conditions, and emergency procedures, including the use of nonverbal signals such as whistles and hand signals. Third, sentiment, which refers to personal experiences, trauma, and emotional support that reinforce awareness of the importance of safety. This study concludes that effective communication plays a crucial role in shaping a culture of safety and shared responsibility among hikers. Synergy between the climbing community and trail managers, supported by technology and good interpersonal communication, is a key factor in creating a safe, orderly, and sustainable climbing environment.